Introduction: Marking the North in the Greek Tradition - Lampinen, Antti (Suomen Ateenan Instituutin Säätiö, 2026)
Out of the four cardinal directions, the ancient ideas regarding the East have undoubtedly received the greatest amount of research. This is understandable, to a degree, since the Greek and Roman experience of the societies of Anatolia, Egypt and the Near East was longstanding feature in the development of their identities. Yet the peoples north of Mediterranean basin - Thracians, Scythians, Celts, and others also played a major role in Greco-Roman thinking about cultural difference, civilisation, and the relationship between humans, nature, and the divine. There are clear heuristic gains, then, in thinking through the northern lens. Moreover, Greco-Roman ways of imagining the North are also important for reception studies, since many elements passed into the Latin and Greek Middle Ages and shaped later representations of northern societies. This volume explores the variety of ways in which the Greeks and in their footsteps, the Romans 'marked' the North and its peoples, rendering them intelligible, distinct, and bounded. Particular attention is given to how the ethnographical tradition operated through knowledge-creation processes, topoi, and established stereotypical beliefs and commonplace imagery.
This rather lengthy introductory chapter sketches out themes and motifs that recur throughout the volume, reviews previous scholarship, and offers definitions for approaching the subject. Though longer than is nowadays common, it has many precedents, and its methodical survey of how antiquity generated knowledge about the North – and of the constituent elements of the ‘boreal imagination’ – is meant to enhance the volume’s coherence and scope.
Marking the North. The Greek Tradition and Its Influence in the Roman Period